1981
DOI: 10.1055/s-0038-1653423
|View full text |Cite
|
Sign up to set email alerts
|

Arachidonic Acid-Induced Chemiluminescence of Human Platelets: Contribution of the Prostaglandin and Lipoxygenase Pathways

Abstract: SummaryTwo signals of chemiluminescence are observed when platelets are exposed to arachidonic acid in the presence of luminol. Three groups of agents interfere with these luminescence responses. Inhibitors of cyclooxygenase, known to augment the turnover of arachidonic acid by lipoxygenase, inhibit the first and enhance the second signal of luminescence.Sodium azide, diamide, NEM, and the endoperoxide analogues U 44069 and U 46619 interfere with the second luminescence signal but not with the first one nor wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1982
1982
1997
1997

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 36 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…There is experimental evidence that lipid peroxides increase platelet sensitivity to agonists (26,27). Furthermore, early reports indicated that CL in platelets arises from prostaglan- din synthesis and lipoxygenase activity (15,16). Worner (15) reported that the chemiluminescence response of platelets exposed to arachidonic acid is dependent on the prostaglandin and lipoxygenase pathways.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is experimental evidence that lipid peroxides increase platelet sensitivity to agonists (26,27). Furthermore, early reports indicated that CL in platelets arises from prostaglan- din synthesis and lipoxygenase activity (15,16). Worner (15) reported that the chemiluminescence response of platelets exposed to arachidonic acid is dependent on the prostaglandin and lipoxygenase pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, early reports indicated that CL in platelets arises from prostaglan- din synthesis and lipoxygenase activity (15,16). Worner (15) reported that the chemiluminescence response of platelets exposed to arachidonic acid is dependent on the prostaglandin and lipoxygenase pathways. Accordingly, the inhibition of platelet CL measured here in the presence of antioxidants indicates metabolization of arachidonic acid under our experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wrrner (39) and Larsen et al (26) showed by use of chemiluminescence that thrombin-stimulated platelets mainly generate OHwhich may injure the endothelial cells. This, indicates that plateletinduced damage to endothelial cells by OH" is not the cause of increased adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…The clear effect of arachidonic acid on CL suggests that eicosanoid formation was not affected by washing the cells with PCEp This is an important point since the critical role played by platelet prostaglandin syn thesis and CL was clearly demonstrated [11]. There is also a negligible contribution of the lipoxygenase pathway if arachidonic acid is of endogenous origin [12], which is not the case when exogenous arachidonic acid is added to pla telets thereby avoiding the time course of arachidonic acid turnover via two signals of CL [13]. Our data, which are in opposition to the reports of Ameisen et al [6] and Pearson and Suarez-Mendez [7], could be due to technical differ ences (such as the use of apyrase or the PGE, concentra tion).…”
mentioning
confidence: 95%